Beyond Learning by Doing : Theoretical Currents in Experiential Education. - Roberts, Jay W. (Taylor & Francis, 2011)
Offering a fresh and distinctive take on a progressive pedagogy, this book examines the notion of experience as it is used in the field of experiential education. As an increasingly popular pedagogical approach, experiential education encompasses a variety of curriculum projects from outdoor and environmental education to service learning and place-based education. While each of these sub-fields has its own history and particular approach, they draw from the same progressive intellectual taproot. Each, in its own way, evokes the power of 'learning by doing' and 'direct experience' in the educa.